One-pot synthesis of ultrahigh performance nanorod structured Co3O4@Fe2O3 anchored on a resonating 2D-carbon with high potential window and surface area for supercapacitors application. Issue 16 (15th August 2021) - Jacob, Otabil Bonsu; Appiagyei, Alfred Bekoe; Han, Jeong In
Abstract: Herein we illustrate a rational scheme to construct nanorod structured Co3 O4 @Fe2 O3 -2DC working electrode for electrochemical capacitor applications. When analyzed as a supercapacitor electrode material, Co3 O4 @Fe2 O3 -2DC at 5 A/g delivered an optimum capacity retention of 96.7%, and a high specific capacitance of 2657.1 F/g at a marginal current density of 1 A/g. Co3 O4 @Fe2 O3 -2DC unparalleled electrochemical performance can be accredited to its unique morphology consigned with a high specific surface area of 532.8 m 2 /g, and the effect of synergy between single-layer practically defect free graphene, and the anchored cobalt and iron metal oxides. The electrode operated within a wide potential window, almost at the limit for aqueous electrolyte system (1.23 V), which makes it merit a high over-potential caption. These results validate Co3 O4 @Fe2 O3 -2DC to be considered as a favorable electrode material, for application in next-generation excellent performance supercapacitors.